Green brand as a marketing instrument: principle, features and parameters. (7th May 2021) - Lyeonov, Serhii; Pimonenko, Tetyana; Chygryn, Olena; Reznik, Oleg; Gaynulina, Regina
In the paper, the authors analysed the approaches to define a green brand. Using the Google Trends, they proved that the terms 'green brand' is more appropriate than 'sustainable', 'environmental' or 'eco brand'. The purpose of the paper is to analyse the critical components of a green brand and its parameters to develop an effective promotion program. Authors developed an approach to estimate green brand which is based on Mark Fetcher model, content analysis and Fishbourne method. Authors analysed the green brand of three industrial companies. The findings proved that the main factors which influence the green brand are the company's transparency not only in financial but also in non-financial results. Thus, published by the companies on the regular basis the non-financial reports provoke the increase of trust among the leading company's stakeholders. It allows attracting additional financial recourses on the company's green development.